If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(k + -3) + -7 = 6k + -1(5k + -2) Reorder the terms: 6(-3 + k) + -7 = 6k + -1(5k + -2) (-3 * 6 + k * 6) + -7 = 6k + -1(5k + -2) (-18 + 6k) + -7 = 6k + -1(5k + -2) Reorder the terms: -18 + -7 + 6k = 6k + -1(5k + -2) Combine like terms: -18 + -7 = -25 -25 + 6k = 6k + -1(5k + -2) Reorder the terms: -25 + 6k = 6k + -1(-2 + 5k) -25 + 6k = 6k + (-2 * -1 + 5k * -1) -25 + 6k = 6k + (2 + -5k) Reorder the terms: -25 + 6k = 2 + 6k + -5k Combine like terms: 6k + -5k = 1k -25 + 6k = 2 + 1k Solving -25 + 6k = 2 + 1k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -25 + 6k + -1k = 2 + 1k + -1k Combine like terms: 6k + -1k = 5k -25 + 5k = 2 + 1k + -1k Combine like terms: 1k + -1k = 0 -25 + 5k = 2 + 0 -25 + 5k = 2 Add '25' to each side of the equation. -25 + 25 + 5k = 2 + 25 Combine like terms: -25 + 25 = 0 0 + 5k = 2 + 25 5k = 2 + 25 Combine like terms: 2 + 25 = 27 5k = 27 Divide each side by '5'. k = 5.4 Simplifying k = 5.4
| x^2-x^2-2+1=7 | | 55r^2+28r-3= | | -y-2=11 | | 2(7x+3)+4=7(2x-1)+2x | | 7y/12-5=9-4y/3 | | 8+4=2(x-12) | | -70-2.25x=182.50 | | 2138=n+38 | | 10x+20xy+7y=100 | | 3x-7=2(x-4)+15 | | 7u-5u=-43 | | y-12=70 | | 3(6x+2)=2(9x-2) | | x+4x-20+5x=180 | | 1/3-3/4 | | 18/5t=-7/2 | | (-10p)+9p=12 | | X/5=3x9 | | 10x+12=9x+32 | | 12x+2=10x+16 | | -9x+3.8=9x+2.0 | | (81x^4y^20)^1/4 | | 10-2(x-4)=3x+1 | | -6y^2-9y=-11 | | 42/x | | (-10)=(-14v)+14v | | 15x-9y=27 | | d-1/12=-2/6 | | 48+84m= | | -12x-9=-14x-15 | | 3/12=3x(s)/a | | 42/x-x=5/2 |